Central Asian modulation of Northern Hemisphere moisture transfer over the Late Cenozoic - Prud'homme, Charlotte; Scardia, Giancarlo [UNESP]; Vonhof, Hubert; Guinoiseau, Damien; Nigmatova, Saida; Fiebig, Jens; Gerdes, Axel; Janssen, Renee; Fitzsimmons, Kathryn E. (Springer, 2021)
Earth's climatic evolution over the last 5 million years is primarily understood from the perspective of marine mechanisms, however, the role of terrestrial feedbacks remains largely unexplored. Here we reconstruct the last 5 million years of soil moisture variability in Central Asia using paleomagnetism data and isotope geochemistry of an 80 m-thick sedimentary succession at Charyn Canyon, Kazakhstan. We identify a long-term trend of increasing aridification throughout the period, along with shorter-term variability related to the interaction between mid-latitude westerlies and the Siberian high-pressure system. This record highlights the long-term contribution of mid-latitude Eurasian terrestrial systems to the modulation of moisture transfer into the Northern Hemisphere oceans and back onto land via westerly air flow. The response of Earth-surface dynamics to Plio-Pleistocene climatic change in Central Asia likely generated terrestrial feedbacks affecting ocean and atmospheric circulation. This missing terrestrial link elucidates the significance of land-water feedbacks for long-term global climate. Late Cenozoic variation in Central Asian hydroclimate resulted from the interaction between mid-latitude westerlies and the Siberian high-pressure system and may have driven terrestrial feedbacks, according to analyses of sediments from Charyn Canyon, Kazakhstan.